Hypomorphic NOTCH3 Alleles Do Not Cause CADASIL in Humans. Issue 11 (7th October 2013) - Rutten, Julie W.; Boon, Elles M.J.; Liem, Michael K.; Dauwerse, Johannes G.; Pont, Margot J.; Vollebregt, Ellen; Maat‐Kievit, Anneke J.; Ginjaar, Hendrika B.; Lakeman, Phillis; van Duinen, Sjoerd G.; Terwindt, Gisela M.; Lesnik Oberstein, Saskia A.J.
Abstract : In this study, we address the previously unresolved issue of the role of hypomorphic NOTCH3 alleles in CADASIL. Based on extensive investigations of two families, we show that hypomorphic NOTCH3 alleles do not cause CADASIL. Furthermore, we describe the first patient who is compound heterozygous for a typical cysteine altering NOTCH3 missense mutation and a large intragenic NOTCH3 deletion who, interestingly, has a phenotype within the normal CADASIL spectrum. ABSTRACT: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by stereotyped missense mutations in NOTCH3 . Whether these mutations lead to the CADASIL phenotype via a neomorphic effect, or rather by a hypomorphic effect, is subject of debate. Here, we report two novel NOTCH3 mutations, both leading to a premature stop codon with predicted loss of NOTCH3 function. The first mutation, c.307C>T, p.Arg103*, was detected in two brothers aged 50 and 55 years, with a brain MRI and skin biopsy incompatible with CADASIL. The other mutation was found in a 40‐year‐old CADASIL patient compound heterozygous for a pathogenic NOTCH3 mutation (c.2129A>G, p.Tyr710Cys) and an intragenic frameshift deletion. The deletion was inherited from his father, who did not have the skin biopsy abnormalities seen in CADASIL patients. These individuals with rare NOTCH3 mutations indicate that hypomorphic NOTCH3 alleles do not cause CADASIL.